Role of Parental Expectations in Determining Child Labour and Schooling - Conan Mukherjee; Rama Pal (Lund University, School of Economics and Management, Department of Economics, 2016)
The paper shows how parental expectations about child's future income affect the incidence of child labour and schooling. We present a theoretical framework where parents decide on the optimal amount of time invested in child education in presence of uncertainty about returns to education. Here, the uncertainty is captured using the probability that parents attach to higher returns after education. Our theoretical findings underscore the need for policy interventions that affect time preferences of parents, for any wage regulations to enhance the extent of child education. On the empirical side, we use a longitudinal survey (Young Lives Survey) for children in Andhra Pradesh, India; to measure the effect of parental expectations on investment in schooling. This longitudinal survey allows us to first, estimate the probability that parents assign to the expectation that their child will get a skilled job in future. And then, we examine the impact of these parental expectations on probability of schooling decision as well as the amount of child's time allocated for studies. Our findings suggest that child's inherent ability, parental education and parents' attitude towards education influence the parental expectations about child's future job. Parental expectations in turn positively affect the investment in human capital. Interestingly, we find a negative impact of the average child wage in community, on both probability of schooling and the proportion of study hours only for boys. This result reflects the ambiguity predicted by our theoretical model, in the effect of child wage on child labour. Our empirical results also indicate that even free education may not encourage child education if parents lack faith in the society to provide skilled jobs.
Keywords: D84; D91; J24; 330; Parental expectations; Uncertainty; Child labour